A report of a child with a deletion (9)(q34.3): a recognisable phenotype?. Issue 7 (July 1997) - Ayyash, H; Mueller, R; Maltby, E; Horsfield, P; Telford, N; Tyler, R
Abstract : We report a case of a male infant who presented with congenital anomalies and was found to have a de novo deletion in the terminal region of the long arm of chromosome 9. He died at the age of 17 weeks of cardiorespiratory failure owing to RSV positive bronchiolitis. A review of previously published reports documented one previous report of a patient with a deletion of (9)(q34.3) and multiple congenital anomalies. Comparison with the previously reported case suggests that the phenotype observed constitutes a clinically recognisable pattern of malformations.